2014
DOI: 10.1038/ncomms4037
|View full text |Cite
|
Sign up to set email alerts
|

Familial Alzheimer’s mutations within APPTM increase Aβ42 production by enhancing accessibility of ε-cleavage site

Abstract: The high Aβ42/Aβ40 production ratio is a hallmark of familial Alzheimer’s disease, which can be caused by mutations in the amyloid precursor protein (APP). The C-terminus of Aβ is generated by γ-secretase cleavage within the transmembrane domain of APP (APPTM), a process that is primed by an initial ε-cleavage at either T48 or L49, resulting in subsequent production of Aβ42 or Aβ40, respectively. Here we solve the dimer structures of wild-type APPTM (AAPTM WT) and mutant APPTM (FAD mutants V44M) with solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
135
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(151 citation statements)
references
References 44 publications
15
135
1
Order By: Relevance
“…The trends observed in the structural ensemble of the C99 23−55 homodimer as a function of lipid membrane composition also provide a partial explanation for the recently observed NMR structure of the C99 23−55 homodimer in DPC micelle (23,42). The structure of C99 15−55 was observed to have a Gly-out topology that differed from the previously proposed Gly-in structures that were based on simulation and solid-state NMR data (7,8,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The trends observed in the structural ensemble of the C99 23−55 homodimer as a function of lipid membrane composition also provide a partial explanation for the recently observed NMR structure of the C99 23−55 homodimer in DPC micelle (23,42). The structure of C99 15−55 was observed to have a Gly-out topology that differed from the previously proposed Gly-in structures that were based on simulation and solid-state NMR data (7,8,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 58%
“…Membrane thickness impacts the processing of APP by γ-secretase and affects the overall production of Aβ peptide and the ratio of Aβ 40 :Aβ 42 . Our results demonstrate that membrane composition does influence membrane thickness, which can alter both the depth of insertion of the peptide into the membrane, and impact the termination of processive cleavage of the TM helix by γ-secretase.…”
Section: Discussionmentioning
confidence: 99%
“…CSPs for Lys 16 may be explained by a recent docking study involving sulindac sulfide and A␤ fibrils that suggested that sulindac sulfide may bind weakly to a shallow, solvent-exposed pocket in the vicinity of Lys 16 and Val 18 and does not interfere with fibrillation (30). This binding mode may, in addition, account for the large REDOR signal detected for the overlapping resonances Val 18 /Val 39 C␥ (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Solution-state NMR structures of the APP-TM (transmembrane) dimer have been solved for the wild-type (17) and a familial mutant (18). NMR and EPR experiments have revealed a potential cholesterol-binding site within the C-terminal Cys 99 sequence and highlight the significance of the GXXXG segments for binding (19).…”
mentioning
confidence: 99%
“…As an initial structure of APP, we used the NMR structure registered in Protein Data Bank (PDB) (PDB ID: 2LZ3 [33]). This structure is a partial structure of APP770 and composed of the 28 amino acids from the Lys699 to Lys726 residues of APP770.…”
Section: Construction Of Stable Structures For App + Curcumin Complexesmentioning
confidence: 99%